2014
DOI: 10.1111/var.12031
|View full text |Cite
|
Sign up to set email alerts
|

Fieldwork, Film, and the Tourist Gaze: Making 农家乐 Peasant Family Happiness

Abstract: Making a film about tourism and being a tourist can often look like the same thing-an outsider with a camera, gazing at a community and people through a lens. And while using a camera in the field can render the ethnographer more legible and logical to one's interlocutors, the production of a film using footage gathered during fieldwork demands an acknowledgment of one's responsibility and relationship to a community and to individuals, qualities not demanded of tourists (or the images they make/take), whose v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Filmmaking allows for movement away from "lingual bias," which I define here as the predisposition to treat signing as primary in deaf communication and the exclusive analytical focus on the production of signs and the structure of sign languages. Ethnographic film is a visual representation of the research; the film is entwined with theory, which drives the editing, pacing, and choices of interviews (Chio 2014(Chio , 2018. Kusters et al (2016, 9) observed, "Deaf signers are often studied and represented in ways that ultimately obscure the visual, embodied nature of their languages, including their expertise, subjective experiences and participation."…”
Section: Film In Linguistic Ethnography As Theory and Methodsmentioning
confidence: 99%
“…Filmmaking allows for movement away from "lingual bias," which I define here as the predisposition to treat signing as primary in deaf communication and the exclusive analytical focus on the production of signs and the structure of sign languages. Ethnographic film is a visual representation of the research; the film is entwined with theory, which drives the editing, pacing, and choices of interviews (Chio 2014(Chio , 2018. Kusters et al (2016, 9) observed, "Deaf signers are often studied and represented in ways that ultimately obscure the visual, embodied nature of their languages, including their expertise, subjective experiences and participation."…”
Section: Film In Linguistic Ethnography As Theory and Methodsmentioning
confidence: 99%